Evidence of Progenitor Cell Lineage Rerouting in the Adult Mouse Hippocampus After Status Epilepticus - Moura, Daniela M. S.; Brandão, Juliana Alves; Lentini, Celia; Heinrich, Christophe; Queiroz, Claudio M.; Costa, Marcos R. (Frontiers in Neuroscience, 2020)
Cell lineage in the adult hippocampus comprises multipotent and neuron-committed progenitors. In the present work, we fate-mapped neuronal progenitors using Dcx-CreERT2 and CAG-CAT-EGFP double-transgenic mice (cDCX/EGFP). We show that three days after tamoxifen-mediated recombination in cDCX/EGFP adult mice, GFP+ cells in the dentate gyrus (DG) co-expresses DCX and about 6% of these cells are proliferative neuronal progenitors. After 30 days, 20% of GFP+ generated from these progenitors differentiate into GFAP+ astrocytes. Unilateral intrahippocampal administration of the chemoconvulsants kainic acid (KA) or pilocarpine (PL) triggered epileptiform discharges and led to a significant increase in the number of GFP+ cells in both ipsi and contralateral DG. However, while PL favored the differentiation of neurons in both ipsi- and contralateral sides, KA stimulated neurogenesis only in the contralateral side. In the ipsilateral side, KA injection led to an unexpected increase of astrogliogenesis in the Dcx-lineage. We also observed a small number of GFP+/GFAP+ cells displaying radial-glia morphology ipsilaterally 3 days after KA administration, suggesting that some Dcx-progenitors could regress to a multipotent stage. The boosted neurogenesis and astrogliogenesis observed in the Dcx-lineage following chemoconvulsants administration correlated, respectively, with preservation or degeneration of the parvalbuminergic plexus in the DG. Increased inflammatory response, by contrast, was observed both in the DG showing increased neurogenesis or astrogliogenesis. Altogether, our data support the view that cell lineage progression in the adult hippocampus is not unidirectional and could be modulated by local network activity and GABA-mediated signaling.